Covert affairs. Season four [videorecording (DVD)] - Gallagher, Peter, 1955-; Perabo, Piper; Gorham, Christopher, 1974- (Universal Studios Home Entertainment, 2014)
Danger, scandal and smoking guns are no match for resourceful CIA operative Annie Walker. When Annie and Auggie, her blind lover and colleague, mix business with pleasure on a trip to Colombia, they ruffle the feathers of local CIA station chief Calder Michaels, whose seemingly fleeting allegiance has major implications for the future of the Domestic Protection Division. Complicating matters, Arthur reveals a 'covert affair' of his own, while Henry's ulterior motives are brought to light.